(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Parallel with the social pedagogue’s professional technologies used in the work with family, implementing provided opportunities of art therapy allows to manage the processes of diagnostics and then curing. They help diagnose the cause of the problem and provide appropriate solutions. The importance of the versatility of work with the family is effective from the aspect of solving the social-psychological, psycho-pedagogical problem in the family, if the social educator is able to not only engage the child but also his/her family members in constructive processes, which will enable each of them to form a value-based transformation of the problem, to appear in the positive side of the solution and realize that each family member is responsible for any problems that arise in the family. Outstanding American art therapists Hanna Kvyatkowska, Judith Rubin, Helen Landgarten, who have developed valuable technology based on their practical research experience for those who practice applied pedagogy or psychology, have works referring to comprehensive researches of family art therapeutic technologies. The article analyzes and presents technologies developed by several modern art therapists, as well as tendencies of art therapy from the aspect of effectiveness of application of family art-technologies. For the first time in this article, family art-technologies are considered as alternatives to making the efficient decisions in the work of a social pedagogue and in the development of a working style. When used by a social pedagogue, family art-technologies can help make effective decisions. They can transmit freer and more creative tone in social pedagogue’s research, diagnosis, problem solving. The tricks of the art-therapeutic technologies discussed in this article can also be used in organizing family counseling.